High-affinity immunoglobulin E receptor expression is increased in large and small airways in fatal asthma - Den Otter, I.; Silva, L. F. F.; Carvalho, A. L. N.; Pires-Neto, R. C.; Annoni, R.; Ferreira, D. S.; Bajema, I.; Van Schadewijk, A.; Rabe, K. F.; Dolhnikoff, M.; Sterk, P. J.; Hiemstra, P. S.; et al. (Clinical and experimental allergy, 2010)
Summary Background IgE and its high‐affinity receptor FcɛRI play an important role in allergy and asthma. The distribution of FcɛRI expression in the airways and within the airway wall, however, is largely unknown. Objective In this study, we aimed to map the distribution of FcɛRI in different layers of large airways (LA) and small airways (SA) in lung tissue from non‐smoking and smoking patients who died of asthma [fatal asthma (FA)] and non‐smoking controls (CTR). Methods Postmortem lung tissue from 24 cases of non‐smoking FA, 13 smoking FA patients and from 19 subjects who died of non‐pulmonary causes (CTR) was immunohistochemically stained for FcɛRI and AA1 (mast cell tryptase marker). The expression of these markers was analysed in inner, muscle, and outer layers of both LA and SA by image analysis. Results FcɛRI expression was higher in non‐smoking and smoking FA compared with CTR in the inner and outer layer of SA. In the outer layer of LA, FcɛRI expression was higher in non‐smoking FA compared with CTR. AA1 was higher in non‐smoking FA compared with smoking FA and CTR in the outer layer of the SA, which was correlated with FcɛRI in this layer. Conclusion Our results show that the expression of FcɛRI is higher in both LA and SA in FA compared with CTR. These differences are predominantly found in the outer layer where they can be attributed in part to the increased mast cell numbers. These results indicate an increased capacity to mount IgE‐mediated reactions in FA, both in LA and SA. Cite this as: I. den Otter, L. F. F. Silva, A. L. N. Carvalho, R. C. Pires‐Neto, R. Annoni, D. S. Ferreira, I. Bajema, A. van Schadewijk, K. F. Rabe, M. Dolhnikoff, P. J. Sterk, P. S. Hiemstra and T. Mauad, Clinical & Experimental Allergy, 2010 (40) 1473–1481.